Yeast ADA2 protein binds to the VP16 protein activation domain and activates transcription. - Silverman, N (1994)
Previously it was shown that yeast ADA2 protein is necessary for the full activity of some activation domains, such as VP16 and GCN4, in vivo and in vitro. These results suggest that ADA2 protein functions as a transcriptional coactivator or adaptor that bridges the interaction between certain acidic activation domains and the basal transcription machinery. Here we present two findings consistent with this model. (i) ADA2 protein interacts with a region of the VP16 acidic activation domain that requires ADA2 for activity in vivo. (ii) ADA2 protein, when fused to a heterologous DNA-binding domain, can stimulate the activity of the basal transcription factors in vivo. This ability of ADA2 to activate transcription is mediated by ADA3, a gene with properties similar to ADA2. These findings suggest that ADA2 protein has at least some of the properties expected of a transcriptional adaptor.